A comparative analysis of the impact of different treatments on Luffa Cylindrica fiber tensile properties - Rania Saadeh; Ayman A. Dawod; Ibrahim Mahariq; Ahmad Qazza; Abdelkader Khentout; Mohamed Kezzar; Mohamed Rafik Sari (PLoS ONE, 2025)
In recent years, there has been a growing demand for environmentally friendly materials as alternatives to synthetic fibers, which pose significant environmental hazards due to their non-biodegradability. Natural fibers, such as Luffa Cylindrica, have gained attention due to their sustainability, lightweight properties, and biodegradability. However, their poor mechanical performance in composite applications limits their widespread use. The novelty of this study lies in the exploration of various treatments aimed at improving the tensile properties of Luffa Cylindrica fibers (LCFs), a relatively under-explored natural fiber. The research investigates the effects of immersion treatments in mineral water, seawater, vinegar (CH₃COOH), sodium bicarbonate (NaHCO₃), and ethanol (C₂H₆O) on the tensile strength, surface morphology, and absorption properties of these fibers. The study highlights that untreated LCFs exhibit superior tensile strength (5.59 MPa) compared to treated fibers. Additionally, the statistical analysis utilizing two-parameter Weibull distribution offers novel insights into the mechanical properties of treated LCFs, confirming significant variations in fiber behavior with different treatments. This study contributes to the understanding of surface modifications that enhance the performance of Luffa Cylindrica fibers in composite materials, a promising step towards their industrial application.